Kinetic parameters for thermal decomposition of supramolecular polymers derived from flunixin-meglumine adducts - Cassimiro, Douglas L. [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Capela, Jorge Manual Vieira [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Capela, Marisa Veiga [UNESP] (Springer, 2011)
Meglumine, (2R,3R,4R,5S)-6-methylaminohexane-1,2,3,4,5-pentol, is a carbohydrate derived from sorbitol in which the hydroxyl group in position one is replaced by a methylamine group. It forms binary adducts with substances having carboxyl groups, which have in common the presence of hydrogen bonding as the main force in the stabilization of these species. During melting, adducts of meglumine with flunixin (2-[[2-methyl-3-(trifluoromethyl)phenyl]amino]pyridine-3-carboxylic acid) polymerize or self-assemble in amorphous supramolecular structures with molecular weights around 2.0 x 10(5) kDa. DSC curves, in a first heating, show isomorphic transitions where the last one at 137 A degrees C for the flunixin-meglumine adduct originated the supramolecular amorphous polymers with glass transition around 49.5 A degrees C. The kinetic parameters for the thermal decomposition step of the polymers were determined by the Capela-Ribeiro non-linear isoconversional method. From data for the TG curves in nitrogen atmosphere and heating rates of 5, 10, 15, and 20 A degrees C min(-1), the E (alpha) and B (alpha) terms could be determined and, consequently, the pre-exponential factor, A(alpha), as well as the kinetic model, g(alpha).
Keywords: Supramolecular polymers; Flunixin-meglumine; Adducts; Non-isothermal kinetics; Thermal decomposition